跳到主文
部落格全站分類:運動體育
f(x)=x^2+xg(x)=2/(x+3)
1. (f-g)(2)(f-g)(x) = f(x) - g(x) = x^2+x - 2/(x+3)(f-g)(2) = 2^2 + 2 - 2/5 = 28/5
2. (f/g)(1)(f/g)(x) = (x^2+x)/[2/(x+3)](f/g)(1) = 2/(1/2) = 4
3. g^2(3)g^2(x) = [2/(x+3)]^2g^2(3) = (2/6)^2 = 1/9
4. (f。g)(1)(f○g)(x) = f(g(x)) = g^2(x)+g(x) = [2/(x+3)]^2 + 2/(x+3)(f○g)(1) = 1/4 + 1/2 = 3/4
5. (g。f)(1)(g。f)(x) = g(f(x)) = 2/(f(x)+3) = 2/(x^2+x+3)(g。f)(1) = 2/5
6. (g。g)(3)(g。g)(x) = g(g(x)) = 2/(2/(x+3)+3)(g。g)(3) = 2/(2/(3+3)+3) = 2/(1/3 + 3) = 2/(10/3) = 6/10 = 3/5
This entry passed through the Full-Text RSS service — if this is your content and you're reading it on someone else's site, please read the FAQ at fivefilters.org/content-only/faq.php#publishers. Five Filters recommends:
線上遊戲排行榜2013/2014,進擊的巨人線上看,candy crush saga外掛,正妹寫真三圍
qhhwzod5rw3gd 發表在 痞客邦 留言(0) 人氣()